Study on carrageenan content and growth of seaweed, Kappaphycus alvarezii, infected by white spot disease using different doses of NPK in Banggai Islands - Poke, Aounorofiq M; Gerung, Grevo S; Montolalu, Roike I (Universitas Sam Ratulangi, 2014)
This study was aimed at assessing the carrageenan content and the growth of seaweed K. alvarezii in white spot disease infection conditions with different doses of NPK in Banggai waters. Results showed that all doses could increase the carrageenan content of the white spot-infected seaweed, with the highest content in treatment D (25 g of NPK/ 10 liters of water), 43.862 ± 19.546, followed by C (20 g of NPK /10 liters of water) 35.685 ± 14.693, B (15 g of NPK/10 liters of water), 23.208 ± 5.992, A (10 g of NPK/10 liters of water),19.132 ± 4.405, and K (without dose), 10.225 ± 2.782, respectively. The highest growth was recorded in treatment D, 401.333 ± 3.215 g, followed by treatment C, 310.000 ± 6.000 g, B, 7.211 g ± 298.000+ 7.211 g, A, 256. 667 ± 11.547 g, and the lowest in control treatment, 218.000 ± 9.849 g, respectively. Penelitian ini bertujuan untuk mengkaji kandungan karaginan dan pertumbuhan dari rumput laut K. alvarezii pada kondisi terkena penyakit white spot dengan dosis NPK yang berbeda di Perairan Kabupaten Banggai. Hasil percobaan menunjukkan bahwa semua dosis mampu meningkatkan kandungan karaginan pada rumput laut yang terinfeksi white spot. Kandungan tertinggi terdapat pada perlakuan D (dosis NPK 25 g/10 liter air) yaitu 43.862±19.546, diikuti perlakuan C (dosis NPK 20 g/10 liter air) 35.685±14.693, B (dosis NPK 15 g/10 liter air) 23.208±5.992, A (dosis NPK 10 g/10 liter air) 19.132±4.405 dan K (tanpa dosis) 10.225±2.782. Pertumbuhan tertinggi terdapat pada perlakuan D yaitu sebesar 401.333 ± 3.215 gram, kemudian diikuti oleh perlakuan C 310.000 ± 6.000 gram, B 298.000 ± 7.211 gram, A sebesar 256.667 ± 11.547 gram, dan terendah pada perlakuan kontrol yaitu sebesar 218.000 ± 9.849 gram.